PEMALSUAN MEREK DAN PENEGAKAN HUKUMNYA (Ditinjau dari aspek Hukum Pidana) - ARYAN, ESTI I (Wacana Hukum, 2009)
Absract: Brand is a very important issue in trading. However, brand counterfeiting often happens to get unlimited advantages for irresponsible and dishonest traders. To make this worse is that the law enforcement for that still faces huge barriers . the barrier comes from the law, the law enforcers and the society. Keywords: law enforcements and law protection